Élaboration d’un modèle de table de concertation pour une gestion participative de la biomasse solide en République démocratique du Congo - Nicolas Onemba Shuku; Évelyne Thiffault; Étienne Berthold (Études Caribéennes)
In this moment, el planeta corre el peligro de preocupare por las externalidades negatives debidas a los climáticos cambios, una gran cantidad de líderes en all el mundo try to project themselves towards greener energies and at lower cost. Those of the DRC are following in the footsteps of offering a ventana de oportunidad para inmensos recursos forestales ante una transición energética para la explotación de biomasa sólida (BS). Without embargo, the challenges to meet its innumerable con el example of the formalization of a collective political option for the improvement of the solid biomass that requires among other things that the scope of intervention of the various stakeholders in the management of the BS sea determined. As a basic preoccupation, we formulate the hypothesis of integrating all the other technical, regulatory and organizational aspects of environmental policies. Además, it is necessary to develop a model of consultation table for the solid biomasa and use the participatory management method of the stakeholders by integrating the factors of sustainability identified as a decisive lever in the management of the solid biomasa in the DRC.The DRC has a mesa redonda of multiple actors under the silvicultura comunitaria. The purpose of this table is to discuss the eficaz establishment of Congolese community forestry in a participatory approach leading de facto to the coexistence of customary law with modern law.While administrative dysfunctions and political governance jeopardize the entire forest system, Law no. Republica Democratica del Congo. With a view to creating the conditions for synergy between the different actors, this article proposes a mesa de concertación para las embarazadas de la BS.